Research in Early Modern Gift Exchange and Personal Writings: On the Possibilities of Anthropologising the Economic History of Central Europe - Čapská, Veronika (Dějiny – teorie – kritika, 2017)
The aim of this contribution is to show that cultural anthropology of gift exchange offers a wide array of analytical instruments that can help us study socio-cultural phenomena in their complexity and dynamics, thereby aiding historians in their efforts to capture changes over time. After briefly addressing the potential contribution of various types of egodocuments to gift exchange research, the author focuses on three epistolographic collections from the seventeenth and first half of the eighteenth century. It is noted that correspondence in itself can be viewed as an exchange of texts, ideas, and often also other accompanying objects. Elaborating on Irma Thoen’s thesis that early modern gift exchange was shaped by a discourse of honour and obligation, the author distinguishes within the relevant correspondence collections between the discourse of service, that of orphanhood and widowhood, and the discourse of ascetic piety. By drawing attention to a wide range of gifting practices, the article moves beyond the long dominant preference for gifts as objects in the earlier Central European historiography